Rice Straw Processing Technology With Incubation Period On Quality Animal Feed Nutrition - Siregar, Dini Julia Sari; Ginting, Friska Br (International Forum of Researchers and Lecturers, 2024)
This study aims to identify the best cellulose, hemicellulose, and lignin content from rice straw processing using fermentation technology with bioactivators EM4, Win Prob, and Microbacter alfaafa 11 at various incubation durations (7, 14, and 21 days) to be used as animal feed. The study was conducted using the Complete Random Design (RAL) method of a 3 x 3 factorial pattern, involving 9 treatments with each treatment repeated three times. The factors tested include: factor A (Type of rice straw processing): 1. Fermentation with EM4; 2. Fermentation with Win Prob; 3. Fermentation with Microbacter alfaafa 11. As well as factor B: Incubation duration (7 days, 14 days, and 21 days). The parameters measured were cellulose, hemicellulose, and lignin content. The results showed that the lowest cellulose content was achieved in the A3B2 treatment (fermentation with Microbacter alfaafa 11 for 14 days) of 36.2591%. A1B1 treatment (fermentation with EM4 for 7 days) resulted in the highest hemicellulose content of 30.4997%. Meanwhile, the lowest lignin content was found in the A3B2 treatment with a value of 15.3618%. In conclusion, the fermentation treatment of rice straw with Microbacter alfaafa 11 for 14 days (A3B2) was the most optimal in reducing the content of cellulose (36.2591%), hemicellulose (25.8671%), and lignin (15.3618%).